Materials and Nanostructures for Light-Matter Interactions in 2d - Yu, Tongcheng (ProQuest Dissertations & Theses, 2021)
2D material is a perfect candidate for electro-optics with its small footprint, tunable optical properties achieved at low applied voltages, unique optical responses, and complementary metal-oxide-semiconductor (CMOS) compatibility. However, direct usage of 2D materials in this field is difficult due to their poor light absorption (less than 10% for graphene and TMDs).It is possible to enhance the interaction of light and 2D material with the help of nanostructures. In this thesis, two different nanostructures have been studied (based on MoS2 and graphene) for high optical modulation depth. A Fabry-Perot (FP) nanostructure was utilized to enhance the absorption of MoS2, which achieved a 6 dB visible light polarization-dependent modulation at a narrow range of the excitonic band of MoS2; Another plasmonic slot waveguide structure integrated with graphene was studied. Relying on the interaction between graphene and the gap surface plasmon (GSP) mode, a modulation depth of 0.12 dB/Âµm was yielded (12% absolute modulation depth) at the telecom wavelength range. The modulation depth of our devices is at the forefront of current optical modulators with the same 2D material.On the other hand, our hybrid nanostructures offer new approaches to characterize the light-matter interactions in 2D materials. We were first to measure the dependence of the n and k spectra for a MoS2 monolayer on the gate voltage with ellipsometry (see Figure 3.6). We found that the absorption coefficient k of monolayer MoS2 is gate-dependent at the excitonic range, and a multi-Lorentzian dispersion model explained this result well; By integrating graphene into the plasmonic slot waveguide structure, we were able to realize a conceptually new method of nanoscale light field 12 imaging with a lateral resolution of ~ 20 nm, based on the photoelectric effect in a p-n junction induced in graphene, which is not subject to the diffraction limited resolution. This new reliable nanoscale light field imaging method could be used for accurate and deterministic light field characterization in nano-optics.Finally, to achieve robust operation of the fabricated devices based on a gated 2D material, the dielectric gate separator is essential as it needs to be stable in a relatively large electrical field. Our work found that the gating properties of the dielectric material strongly depend on the dielectric fabrication technique. The dielectric performance of two widely used dielectric materials, hafnia and alumina (HfO2 and Al2O3), fabricated by two different methods (electron beam evaporation and atomic layer deposition), was studied, and we found a dramatic change in the hysteresis properties of graphene gating for these two fabrication methods. X-ray photoelectron spectroscopy (XPS) provided a clue that the gating properties strongly depend on the presence of oxygen vacancies.